2019
DOI: 10.1111/pce.13667
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungus Falciphora oryzae promotes lateral root growth by producing indole derivatives after sensing plant signals

Abstract: The endophytic fungus Falciphora oryzae was initially isolated from wild rice (Oryza granulata) and colonizes many crop species and promotes plant growth. However, the molecular mechanisms underlying F. oryzae‐mediated growth promotion are still unknown. We found that F. oryzae was able to colonize Arabidopsis thaliana. The most dramatic change after F. oryzae inoculation was observed in the root architecture, as evidenced by increased lateral root growth but reduced primary root length, similar to the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 93 publications
(119 reference statements)
2
24
2
Order By: Relevance
“…that modulation in RSA was accompanied by regulation of the hormonal (indole acetic acid, abscisic acid, gibberellic acid) balance in roots (Liu and Wei 2019). Sun et al (2019) demonstrated the role of the endophytic fungus Falciphora oryzae in RSA development (enhanced lateral root formation) and suggested that endophytes up regulate the genes responsible for auxin synthesis and signaling.…”
Section: Accepted Articlementioning
confidence: 99%
“…that modulation in RSA was accompanied by regulation of the hormonal (indole acetic acid, abscisic acid, gibberellic acid) balance in roots (Liu and Wei 2019). Sun et al (2019) demonstrated the role of the endophytic fungus Falciphora oryzae in RSA development (enhanced lateral root formation) and suggested that endophytes up regulate the genes responsible for auxin synthesis and signaling.…”
Section: Accepted Articlementioning
confidence: 99%
“…The small moleculars secreted by roots such as amino acids, organic acids, sugars and secondary metabolites can specifically promote the growth of some soil microorganisms, causing the migration of soil microbial communities [47]. For instance, Falciphora oryzae colonized Arabidopsis roots by sensing signalling molecules from its roots, and then promoted the lateral root growth of Arabidopsis through biosynthesis of indole derivatives [48]. We speculated that rhizosphere microbes can also directly or indirectly envolved in and influence the growth and metabolism process of hosts.…”
Section: Potentially Mechanistic Associations Between Rhizosphere Micmentioning
confidence: 99%
“…These results suggested that the exogenous application of CaCl 2 and IAA in the early developmental stage of fruiting body can affect the primordium differentiation and stipe development, especially the effect of CaCl 2 on inhibiting the stipe development. There are also reports about the effects of plant hormones on fungi development [34][35][36][37]. Considering the above analysis, we chose 1 mM of calcium chloride (CaCl2), 1 mM of sodium bicarbonate (NaHCO3), 0.01 mM of Indole-3-acetic acid (IAA), and 0.01 mM of gibberellin 3 (GA3) as the exogenous inducer to apply on the primordium of the fruiting body.…”
Section: Ca 2+ Plays a Regulatory Role In The Primordium Differentiationmentioning
confidence: 99%